(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: In the present century, women seem to flood into every industry/department on par with men with their knowledge and skill. The working woman’s job title, demands, and challenges she faces often result in incompatibilities between the necessities felt at the workplace and home leading to conflicts and loss of work-life balance (WLB). Eventually, a work-life balance is said to exist if the workplace and non-work domains have a proper compatibility. Methods: A hospital-based cross-sectional study has been conducted among married female healthcare workers in the tertiary care hospital during the period November 2022 to April 2023. The healthcare workers included were Doctors, Nurses, Pharmacy staff, and lab technicians. A sample size 318 was derived and samples were drawn by stratified random sampling method. The chi-square test was employed to find an association in IBM SPSS v21. Results: Only 28.3% of the healthcare workers had adequate work-life balance and the majority (66 %) cited family factors as the key factor influencing their work-life balance. Statistically significant association (p<0.05) has been established for characteristics like occupation, marital status, type of family, presence of children, type of duty, place of work and travel time. Conclusion: A series of focus group discussions can be conducted as it serves as a forum for sharing ideas, concerns and information on work-life balance. Institutions can support their staff by developing flexible working schedules and also by ensuring that workplace demands are not penetrating their personal life.